Analysis of the Brucella melitensis epidemic in Xinjiang: genotyping, polymorphism, antibiotic resistance and tracing - Xiaowen Yang; Yan Liu; Na Li; Xiaowei Peng; Yinghui Zhang; Xiaoqian Zhang; Lin Liang; Zengjie Bian; Hui Jiang; Jiabo Ding (BMC, 2024)
Abstract Brucella spp. are facultative intracellular pathogens that cause zoonosis- brucellosis worldwide. There has been a trend of the re-emergence of brucellosis worldwide in recent years. The epidemic situation of brucellosis is serious in Xinjiang. To analyze the epidemic situation of Brucella spp. in Xinjiang among humans and animals, this study identified 144 Brucella isolates from Xinjiang using classical identification and 16 S rRNA sequencing. MLVA, drug resistance testing, and wgSNP detection were also performed. At the same time, analysis was conducted based on the published data of Brucella isolates worldwide. The results showed that the dominant species was B. melitensis biovar 3, which belonged to GT42 (MLVA-8 typing) and the East Mediterranean lineage. The correlation among isolates was high both in humans or animals. The isolates in Xinjiang exhibited higher polymorphism compared to other locations in China, with polymorphism increasing each year since 2010. No amikacin/kanamycin-resistant strains were detected, but six rifampicin-intermediate isolates were identified without rpoB gene variation. The NJ tree of the wgSNP results indicated that there were three main complexes of the B. melitensis epidemic in Xinjiang. Based on the results of this study, the prevention and control of brucellosis in Xinjiang should focus on B. melitensis, particularly strains belonging to B. melitensis bv.3 GT42 (MLVA-8 typing) and East Mediterranean lineage. Additionally, the rifampicin- and trimethoprim-sulfamethoxazole- resistance of isolates in Xinjiang should be closely monitored to avoid compromising the therapeutic efficacy and causing greater losses. These results provide essential data for the prevention and control of brucellosis in Xinjiang and China. Although the isolates from Xinjiang have significant characteristics among Chinese isolates and can reflect the epidemiological situation of brucellosis in China to some extent, this study cannot represent the characteristics of isolates from other regions.